Competing Values Framework Application to Organizational Effectiveness in Voluntary Organizations: A Case Study. (October 2015) - Grabowski, Louis; Neher, Cathy; Crim, Timothy; Mathiassen, Lars
Although the widely used Competing Values Framework (CVF) has attracted considerable attention in the literature and has proven useful as an approach to organizational effectiveness, we know little about how it applies to voluntary organizations. We therefore combined CVF with rigorous action research methodology to analyze the organizational effectiveness of Right in the Community (RitC), a voluntary agency serving the developmentally disabled. As our results show, CVF's three dimensions of organizational focus, structural preference, and managerial concern helped us improve the organization's management of scarce resources, organizational structure and governance, and innovative capabilities. During the collaboration, we also observed tensions between heart and head that were particularly relevant for improving organizational effectiveness at RitC. We therefore propose extending CVF for voluntary organizations with a fourth dimension: motivational trait.